Relationship of the presence of oral lesions in type ii diabetic patients and the use of dental prosthesis. Bibliographical Review - Tumbaco Cedeño, Gabriela Dayanara (2025)
The relationship between the presence of oral lesions in type II diabetic patients and the use of dental prostheses, with the focus on how these lesions affect quality of life and are compared with non-diabetic patients. Research reveals that diabetic patients who wear dentures face a higher prevalence and severity of oral lesions, such as ulcers and candidiasis, due to factors such as poor glycemic control and xerostomia. These conditions not only aggravate the onset of oral problems, but also have a significant negative impact on your quality of life. Comparative analysis shows that, compared to non-diabetic patients, diabetics have a higher frequency of infections and a greater impact on general health, exacerbating systemic complications and decreasing general well-being. In this sense, the main objective of the present bibliographic review was to determine the relationship between type II diabetes mellitus, the use of dental prostheses and the presence of oral lesions in adult patients. The literature analyzed highlighted the urgent need for specific preventive and corrective strategies for diabetic patients who use dental prostheses, in order to improve their oral health and quality of life. They conclude in the improvement of glycemic control, the rigorous implementation of oral hygiene, and more frequent monitoring for the effective management of oral lesions.